The multidisciplinary approach to ovarian tumours in children and adolescents. (December 2019) - van Heerden, J.; Tjalma, W.A.
Abstract: Ovarian tumours in children and adolescents are rare diseases. Although the majority of tumours are benign, the diagnosis and management present various challenges that require a wide range of expertise. The multidisciplinary team ensures not only accurate diagnosis and correct and minimally invasive management, but also minimal psychological impact and the preservation of fertility. This article outlines the multidisciplinary team approach to ovarian masses in children and adolescents. The team includes paediatric oncologists, gynaecological surgeons, pathologists, radiologists, fertility experts, geneticists and psycho-social services.